Consumer behaviour : a European perspective - Solomon, Michael R., 1956-; Askegaard, Søren, 1961-; Hogg, Margaret K., ....-; Bamossy, Gary J., 1949- (Harlow : Pearson, 2019)
Now in its seventh edition, Consumer Behaviour: A European Perspective provides the most comprehensive, lively and engaging introduction to the behaviour of consumers in Europe and around the world. The new slimline edition has 13 chapters, maintaining its breadth of coverage and making it ideal for second- and third-year undergraduates as well as Master's students.
Keywords: Consumentengedrag